PENGARUH ADVERSITY QUOTIENT TERHADAP HASIL BELAJAR DARING IPA SISWA KELAS IV SD SEKECAMATAN KLIRONG TAHUN AJARAN 2020/2021 - Laelatus Soimah; Suhartono Suhartono; Wahyudi Wahyudi (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
Adversity quotient is one of the internal factors affecting student’s online learning outcomes for natural science. The study aimed to examine positive effect of adversity quotient on online learning outcomes for natural science to fourth grade students of public elementary schools in Klirong Sub-district in academic year of 2020/2021 and to determine the contribution of adversity quotient on online learning outcomes for natural science to fourth grade students of public elementary schools in Klirong Sub-district in academic year of 2020/2021. It was a quantitative research with simple linear regression method. The population were 749 fourth grade students and the samples were 261 fourth grade students throughout Klirong Sub-district. Data collection techniques used questionnaires and tests. Data analysis used SPSS 25 version. The results showed that: (1) there was a positive and significant effect of adversity quotient on online learning outcomes for natural science to fourth grade students of public elementary schools in Klirong Sub-district in academic year of 2020/2021. The adversity quotient contributed 22% with a value of Sig. 0.000 < 0.05. It meant that the higher student's adversity quotient, the higher student's natural science learning outcomes and vice versa; (2) the adversity quotient contributed 22% on online learning outcomes for natural science to fourth grade students and the remaining 78% was influenced by other factors.